Dimensions and dynamics of microfinance membership overlap – a micro study from Bangladesh - Chaudhury, Iftekhar A.; Matin, Imran (Small Enterprise Development, 2019)
The microfinance market of Bangladesh is getting rapidly crowded. In certain areas there is also quite high incidence of households taking loans from a number of microfinance providers. Why is this happening? How does it affect the providers? What should be done? These are some of the questions that this paper begins to address based on data collected from BRAC's operations in Tangail. We find that a number of crises often gives rise to an urgent need for lump sums of cash, and this is why households often need access to several loan sources. Though repayment irregularity is found to be on the increase, somehow it is being managed from turning into a major default problem, suggesting a level of in-built resilience of the system. This needs further research. In terms of what should be done, we chalk a broad agenda consisting of better information-sharing mechanisms and developing better risk-responsive financial products. In this sense, the phenomenon of multiple microfinance membership is as much an opportunity as it is a challenge.